The Influence of Agent Competence and Trust on Customer Loyalty to Sharia Life Insurance (Study at PT. Prudential Life Assurance Binjai Branch - Ayuni, Putri; Ahmadi Bi Rahmani, Nur (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2023)
The purpose of writing this article is to examine influence agent competency and trust have on customer loyalty for Sharia life insurance (Case Study of PT Prudential Life assurance branch of Binjai). This study applies a quantitative descriptive method with multiple linear regression analysis. This study applies data processing according to statistical mechanisms and then interpreted in the form of numbers obtained from the instrument in the form of a questionnaire. This study has subjects in the form of customers from PT Prudential Life assurance Binjai branch and objects in the form of the influence of agent competence and trust on consumer loyalty. The population of this study is a number of 80 Sharia life insurance customers and applies a sampling technique in the form of a saturated sample. This is because the population is under 100 people so that all of them are drawn as research samples. Based on the results of data processing obtained through the t test obtained a count of 3.798 and a significance of 0.000. So the interpretation is tcount>ttable (3.798>1.29). The first hypothesis is accepted so that competence has a positive and significant effect on customer royalties of PT Prudential Life assurance Binjai branch. Then the results of subsequent tests on the trust variable obtained t count of -2.295 and a Sig value of 0.024. So it is interpreted that tcount<ttable (-2.295<1.29) so that the second hypothesis is rejected because trust has a negative and significant effect on consumer loyalty.